Challenges for Ukraine’s cyber security: National dimensions - Katerynchuk, Pavlo (Eastern Review, 2019)
The usage of information as a weapon in the foreign and domestic policies of Russia is not a new phenomenon. Still, the sophistication and intensity of it grow with each passing year. Recently the EU and USA have realized the powerful latent influence of Russian media and propaganda, including on electoral processes and the activities of State administration. They have realized that Russian disinformation poses a serious threat to the United States and its European allies, first and foremost with regard to Poland, the Baltic States and Ukraine. Moreover, unlike Soviet propaganda, the modern methods of the Russian information war do not rudely promote the agenda of the Kremlin. Instead, they aim to confuse, daze and divert citizens from supporting the EU and Ukraine. Russia seeks to undermine the support for European values; producing disarray among European allies in order to increase its influence. Ethnic, linguistic, regional, social and historical contradictions and stereotypes are used for this purpose. As current experience shows, Russian advocacy efforts in Europe make up an important part of their hybrid approach to the projection of force. Despite the fact that the crisis in Ukraine for the first time drew the attention of the West to the importance and real meaning of the information campaign in Russia, the Kremlin’s use of disinformation was launched long before the crisis. Russia carefully and purposefully prepared an information war against Ukraine.